Materials and Fabrication Processes for Transient and Bioresorbable High‐Performance Electronics. (11th April 2013) - Hwang, Suk‐Won; Kim, Dae‐Hyeong; Tao, Hu; Kim, Tae‐il; Kim, Stanley; Yu, Ki Jun; Panilaitis, Bruce; Jeong, Jae‐Woong; Song, Jun‐Kyul; Omenetto, Fiorenzo G.; Rogers, John. A.
Abstract Materials and fabrication procedures are described for bioresorbable transistors and simple integrated circuits, in which the key processing steps occur on silicon wafer substrates, in schemes compatible with methods used in conventional microelectronics. The approach relies on an unusual type of silicon on insulator wafer to yield devices that exploit ultrathin sheets of monocrystalline silicon for the semiconductor, thin films of magnesium for the electrodes and interconnects, silicon dioxide and magnesium oxide for the dielectrics, and silk for the substrates. A range of component examples with detailed measurements of their electrical characteristics and dissolution properties illustrate the capabilities. In vivo toxicity tests demonstrate biocompatibility in sub‐dermal implants. The results have significance for broad classes of water‐soluble, "transient" electronic devices.